Jatta - Hale, Jenny (Scholastic Press, 2009)
Jatta is a princess in the kingdom of Alteeda, but her life is no fairytale. Her mother was slain by werewolves when Jatta was three, and now at the age of 14, she has discovered that the werewolves left their curse on her
Keywords: Werewolves / Juvenile fiction; Young adult fiction; Werwolf; Prinzessin; Jugendbuch